Tuning Porphyrin Assembly and Electrochemical Catalytic Activity with Halogen Substituents - Kawamoto, Teppei (Langmuir : the ACS journal of surfaces and colloids, 2015)
The adlayers of three metalloporphyrins, 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin cobalt(II) (CoTMePP), 5,10,15,20-tetrakis(4-bromophenyl)porphyrin cobalt(II) (CoTBrPP), and 5,10,15,20-tetrakis(4-iodophenyl)porphyrin cobalt(II) (CoTIPP), on Au(111) were investigated at the solid-liquid interface under electrochemical conditions. In situ scanning tunneling microscopy (STM) was employed to investigate the adlayer structures of CoTMePP, CoTBrPP, and CoTIPP in HClO4 solution. Highly ordered adlayers of the three metalloporphyrins were formed on the Au(111) electrode surface by simple immersion into benzene solutions containing each compound. The adlayer structure of the three cobalt porphyrin derivatives was influenced by the functional group on the phenyl moieties. In particular, a characteristic molecular assembly of CoTIPP molecules was found on Au(111) as a result of the I···I interactions between CoTIPP molecules. The adlattice constants increased in the order -OCH3 < -Br < -I in the phenyl groups. The in situ STM observations showed that the CoTMePP adlayer changed during positive potential manipulation in 0.1 M HClO4, whereas these adlayers were stable in the potential range from 0.90 to 0 V versus the reversible hydrogen electrode. A dependence upon the functional groups among the three CoTPP derivatives was clearly found in the adlattice constants and O2 reduction potentials, revealing that the two-dimensional (2D) molecular assembly and electrochemical activity for dioxygen reduction of the tetraphenylporphyrin derivatives can be tuned by introducing functional groups at the 4 positions of the phenyl moieties, especially iodine substituents